Perspectival representation in DSGE models - Kawalec, Paweł (Economics and Business Review, 2017)
DSGE models (Introduction) have recently been criticized by P. Romer (2016) as pseudoscientific (Section 1). Their dominance is attributed to the uncritical “deference to authority” that has dominated macroeconomics “for the last 30 years”. In contrast, the paper aims to support the widespread view that – their problems notwithstanding – DSGE models meet the epistemic standards of scientific research. The argument turns on the recent advancements in theories of scientific representation (Section 1) and of empirical grounding (Section 2). The latter is illustrated with a historical case, which also substantiates Romer’s constructive point on the role of theory in design of measurements.